Change in lung function abnormalities in patients treated for first ever pulmonary tuberculosis in Dar es Salaam, Tanzania - Reinhard Elisania Lema; Grace Ambrose Shayo; Zuhura Nkrumbih; Tumaini Joseph Nagu (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Objectives: To document abnormalities in pulmonary function (PF) and associated factors in patients completing treatment for microbiologically confirmed, first-ever pulmonary tuberculosis (PTB).From August 2020 to May 2021, we recruited 332 patients aged ≥15 years. PF was evaluated at baseline and at treatment completion. The Wilcoxon signed-rank test was used to compare median PF changes between baseline and treatment completion. A log-binomial regression model was used to determine factors associated with abnormal PF at treatment completion. Statistical significance was set at p ≤ 0.05. Results: Abnormal PF was observed in 142 of 300 (47.3 %) patients who completed the study. Being male (RR [95 % CI] = 1.22 [1.19–2.23]), underweight (RR = 1.49 [1.13–1.95]), having lung cavitation (RR = 1.90 [1.29–2.78]), and lung fibrosis at baseline (RR = 2.16 [1.32–3.53]) were significantly associated with abnormal PF. The median (IQR) FEV1 at treatment completion was 2.33 L (0.90–4.23 L) and FVC was 3.05 L (1.10–7.50 L), both significantly higher than FEV1 of 2.18 L (0.20–5.70 L) and FVC of 2.82 L (0.26–7.05 L) at treatment initiation (p < 0.05 for both). Conclusion: Approximately half of the patients had abnormal PF at treatment completion. Underweight patients, males, and those with lung cavitation at treatment initiation are more likely to have abnormal PF at the end of treatment and may require special attention.